I survived : the Japanese Tsunami, 2011 - Tarshis, Lauren; Ball, Georgia (I survived (Graphic novel series), 2025)
A massive earthquake and devastating tsunami hit Japan while Ben is visiting his late father's hometown, pulling Ben's family apart and leaving him stranded in a strange country during an epic disaster.